Effectiveness of Mind Mapping as Digital Brainstorming Technique in Enhancing the Writing Skills of Indian Students - Jaiprakash, Heethal; Hishan, Sanil S; Ramakrishnan, Suresh (International Journal of Psychosocial Rehabilitation, 2020)
Writing is an essential means of contact between individuals and society. This is an important part of contact. Developing a healthy mindset of future teachers would allow them to become internationally competent. The research focused on the utility of interactive brainstorming using visual modeling to improve students ' writing success and attitudes. The thesis employed an experimental testing method before the evaluation after the evaluation. The participants included 25 students. The experimental process lasted eight days and samples were taken before and after the operation. The degree of significant differences was determined by the t-test based study. On the basis of the findings, it revealed that the technique for mapping the mind has a considerable effect on respondents ' writing efficiency, although the writing attitude before and after implementation did not vary significantly. This indicates that students have developed a high degree of attitude towards learning. The research concluded that mind mapping is an important method for optimizing student writing efficiency.